The C57Bl/6J mouse strain is more susceptible to angiotensin II-induced aortic aneurysm formation than C57Bl/6N - Wortmann, Markus; Arshad, Muhammad; Peters, Andreas; Hakimi, Maani; Böckler, Dittmar; Dihlmann, Susanne (Atherosclerosis, 2021)
Background and aims - Genetic variations between C57Bl/6 mouse substrains are highly relevant to the investigation of cardiovascular disease. We here assessed whether these variations have an impact on the incidence of abdominal aortic aneurysms (AAA) in C57Bl/6J and 6 N mice. - Methods - AAA were induced by subcutaneous infusion of 1500 ng/kg*min Angiotensin-II for four weeks in six-month-old male CB57Bl/6J and 6N mice. Aortic smooth muscle cells (VSMC) were isolated from untreated animals for in vitro analysis. - Results - C57Bl/6J mice are more susceptible to AAA formation (76.5% vs. 7.1%, p = 0.0002). C57Bl/6J VSMC expressed more pro-inflammatory molecules such as Nlrp3, Aim2 and NF-κB. Additionally, these cells presented significantly higher levels of NADP/NADPH and oxidative DNA modifications, as indicated by 8-OHdG-staining, compared to C57Bl/6N VSMC. - Conclusions - In contrast to previous reports, we present evidence that six-month-old C57BL/6J, but not C57BL/6N mice develop AAA. In accordance with the deficiency of nicotinamide-nucleotide-transhydrogenase (Nnt), C57BL/6J VSMC displayed increased oxidative stress, oxidative DNA damage and a stronger inflammatory phenotype than C57BL/6N VSMC.
Available online 1 December 2020
Gesehen am 30.03.2021